Geographic Information and Covid-19 Outbreak Does the spatial dimension matter? - Michele Campagna (TeMA: Journal of Land Use, Mobility and Environment, 2020)
The Covid-19 pandemic in Europe started its outbreak in Italy in January 2020, and since early March 2020, it rapidly spread in most European Countries with growing diffusion rates. EU Countries applied lock-down measures accordingly. While Government across Europe relied in experts’ advice, scientific advisory teams were often lead by virologists and epidemiologists, and no evidence is easily found about the involvement of experts in spatial planning and design in emergency response. Often in the uncertainty of a new hazard emergency response, lock-down measures were based on national or regional scale planning, applying to large administrative units boundaries with little or no local differentiations.